‘Paradoxes of the Panoscope’: ‘Walking’ Stewart and the Making of Keats’s Ambivalent Imagination - Grovier, Kelly (Romanticism and Victorianism on the Net, 2008)
AbstractThis articles seeks to recover a lost visual device proposed in 1812 by the English traveller and materialist philosopher John "Walking" Stewart, and to explore how the imaginary apparatus participated in a prevailing intellectual climate of ambivalence to which Keats's imagination was particularly responsive. Stewart's curious contraption, the "panoscope", was fashioned as a pseudo-scientific, quasi-medical implement which could enable the aperture of human perception to resolve with a kind of rationally achieved omniscience the material reality that constitutes the eternal interchange between substances in states of "patiency" and "agency—life and death. The inherent ambivalence of panoscopic vision towards the prevalence of life or death, it is argued, came to distinguish much of Keats's writing in the last phase of his career as the promise of transmutation between literal and literary states of "composition" and "decomposition" became at once a comfort and anxiety for him.